Availability and Quality of Assessment Instruments on Patient-Centredness in the Multimorbid Elderly (AQuA-PCE): a study protocol of a systematic review. Issue 2 (5th February 2020) - Glattacker, Manuela; Kanat, Manuela; Schaefer, Jonas; Motschall, Edith; Kivelitz, Laura; Voigt-Radloff, Sebastian; Dirmaier, Joerg
Abstract : Introduction: Elderly, multimorbid patients are a primary target group for patient-centred care, and fostering patient-centredness (PC) in this group has been associated with different healthcare aims such as safety and quality of healthcare. However, evidence on effects of patient-centred interventions is still limited and mixed. In part, the lack of consistent evidence has its roots in a conceptual uncertainty of the term 'PC', which also hampers the development of assessment tools for PC. Consequently, reviews on assessment instruments of PC reveal problems regarding the quality of identified assessment instruments and regarding their comparability. Some of these reviews focus on the elderly. However, while the concept of multimorbidity is partly inherent, this focus is not explicit in any of the reviews. The aim of this systematic review is to identify assessment instruments of PC in the multimorbid elderly, using a subgroup-specific definition of PC ('subgroup-specific integrative model of PC') as the conceptual underpinning, and to provide a critical quality appraisal of their psychometric properties. Methods and analysis: A comprehensive systematic literature search for assessment tools on PC will be conducted in the MEDLINE, CINAHL, EMBASE, PsycINFO, Web of Science and PSYNDEX electronic databases. The search strategy will be informed by the subgroup-specific integrative model of PC. The electronic literature search will be complemented by a hand-search combining citation tracking, search in project databases, and contacting authors from relevant studies/reviews. The literature search (systematic and hand-search) will cover the period from November, 2018 to December 2019. The retrieval of relevant studies will be conducted via title screening, abstract screening, and full-text eligibility assessment applying defined inclusion criteria. Full texts will be independently assessed by two team members. Data from the included articles will be extracted using a standardised extraction form and evaluated based on the COSMIN methodology for systematic reviews of patient-reported outcome measures, which focuses on the methodological quality of included studies as well as on the measurement properties of the assessment instruments. Data extraction and quality assessment will be conducted by two independent reviewers. Ethics and dissemination: The study has received approval from the Ethics Committee of the University of Freiburg (reference number 587/17). The results of the project will be disseminated via scientific oral presentations at national and international conferences and will be published in scientific journals. Trial registration numbers: CRD42018084057; DRKS00013309.